Police officer procedural justice self-assessments: do they change across recruit training and operational experience? - Fildes, Alistair (Policing and society, 2019)
With the increased focus on applying procedural justice into policing practice, a small number of studies have examined officer attitudes to procedural justice. These studies have measured a diverse range of attitudinal concepts - from officers’ alignment to procedural justice principles, to the perceived effectiveness of the principles in obtaining compliance from the public. A concept of particular interest is officers’ sense of themselves as acting in a procedurally just manner. As police work is characterised by a high degree of discretion in how officers interact with the public, measuring how such procedural justice self-assessments change over time might indicate hindrances to the longer term uptake of procedural justice. Additionally, understanding what factors influence positive procedural justice self-assessments will assist police organisations in developing officers who identify as procedurally just. This study explores how officers’ procedural justice self-assessments change through recruit training and after officers have become operational. Using longitudinal survey data from Queensland Police recruits collected at the beginning of recruit training (n = 501), at the end of training six months later (n = 331), and after one year of operational experience (n = 152), this study finds that recruits’ procedural justice self-assessments decrease substantially by the end of training, but change little after officers become operational. Further, positive procedural justice self-assessments are predicted predominantly by self-assessed interpersonal skills more so than other attitudinal or demographic measures. The findings suggest that if police organisations wish to develop procedurally just officers, efforts should be concentrated toward improving recruits’ interpersonal skills when dealing with the public.